Behind the choices: Loss aversion's impact on students' course selection - Zaiton Osman; Izyanti Awang Razli; Phang Ing @ Grace (Malaysian Journal of Social Sciences and Humanities (MJSSH), 2023)
This study investigates how the concept of loss aversion affects the decision-making process of students when they choose their courses at Universiti Malaysia Sabah. The primary focus of this research is to understand the impact of factors such as individual interests, career aspirations, and the reputation of lecturers on the degree of loss aversion experienced by students during their course selection. To gather data, the study employed purposive sampling, targeting third-year students from ten different academic programs. Questionnaires were administered, and data analysis was carried out using SPSS version 28 and SmartPLS 4.0. The findings of the study highlight a noteworthy negative correlation between students' career aspirations and the presence of loss aversion in their course selection decisions. Simultaneously, the research indicates that personal interests and the reputation of lecturers do not exert a significant influence on the manifestation of loss aversion in course selection among students at Universiti Malaysia Sabah.